The Improvement of Sharia Financial Literacy Through Sharia-Based Mosque Financial Management Training for Mosque Administrators in Handio Village - Lubis, Aminah; Nasution, Enni Efrida; Hasibuan, Muhammad Sarkawi; Nasution, Salsabilah; Hasibuan, Ulfa Khairani (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
Low levels of knowledge and understanding of sharia-based financial management within mosque environments remain a major obstacle in achieving transparent and accountable financial governance. This study aims to enhance sharia financial literacy among mosque administrators through training in mosque financial management aligned with sharia principles. The training was conducted in a structured manner and involved all mosque administrators in Handio Village. The results show that after each training session, there was a notable improvement in the administrators' understanding of fundamental sharia financial principles, such as honest financial recording, trustworthy management of social funds, and more orderly and transparent financial reporting. This activity also fostered collective awareness of the importance of sharia-based financial management in strengthening the congregation's trust in the mosque institution. Therefore, the training proved effective in promoting sharia financial literacy at the village level.